The efficacy of group cognitive behavioural therapy (CBT) for adults with a history of childhood abuse : a single-case experimental study - Vigdís Margrétard. Jónsdóttir 1988- (2022)
Background and objectives: Individual cognitive behavioural therapies are effective for treating adults with complex PTSD (CPTSD) (Coventry et al., 2020; Karatzias et al., 2019). Research on the effectiveness of group CBT for this patient group is sparse. The study aimed to evaluate the effectiveness of an 18-session CBT-based group therapy for adults with a history of childhood abuse (Kennerly et al., 2014). Methods: Subjects in this study were ten women with a history of childhood abuse who were service users of the Vocational Rehabilitation Fund (VIRK) in Iceland. Participants' symptoms of depression, anxiety, and stress were measured using the Depression Anxiety Stress Scale (DASS-21 and DASS-42), CPTSD symptoms using the International Trauma Questionnaire (ITQ), and self-esteem using the Robson-SCQ. Symptom measures were obtained during baseline, after each therapy session, and post-treatment. Changes in symptom measures were evaluated using a single-case multiple baseline design and Tau-U calculations. Results: The group CBT was effective in reducing CPTSD symptoms in six of the nine participants that completed the treatment. Limitations: The number of participants in the study was relatively small. All participants started the intervention at the same time which poses a threat to internal validity. Conclusions: The results indicate the initial efficacy of group CBT for adults with a history of childhood abuse. Keywords: childhood abuse, complex post-traumatic stress disorder, group cognitive-behavioral therapy.